Looking into sewage: how far can metagenomics help to detect human enteric viruses? - Schaeffer, Julien; Desdouits, Marion; Besnard, Alban; Le Guyader, Françoise S. (Frontiers in Microbiology, 2023)
The impact of human sewage on environmental and food contamination constitutes an important safety issue. Indeed, human sewage reflects the microbiome of the local population, and a variety of human viruses can be detected in wastewater samples. Being able to describe the diversity of viruses present in sewage will provide information on the health of the surrounding population health and will help to prevent further transmission. Metagenomic developments, allowing the description of all the different genomes present in a sample, are very promising tools for virome analysis. However, looking for human enteric viruses with short RNA genomes which are present at low concentrations is challenging. In this study we demonstrate the benefits of performing technical replicates to improve viral identification by increasing contig length, and the set-up of quality criteria to increase confidence in results. Our approach was able to effectively identify some virus sequences and successfully describe the viral diversity. The method yielded full genomes either for norovirus, enterovirus and rotavirus, even if, for these segmented genomes, combining genes remain a difficult issue. Developing reliable viromic methods is important as wastewater sample analysis provides an important tool to prevent further virus transmission by raising alerts in case of viral outbreaks or emergence.